Gender Translation in the Directions of Product Labels from English into Arabic - Khoshafah, Mohammed Abduh Nagi Ali; al-Shamiri, Abdul-Kawi Hizam M.; Noaman, Abdulrahman Ahmed Mohammed; Al-Nazary, Reema Ali (Arts for Linguistic & Literary Studies, 2024)
The study at hand aimed at investigating the techniques that are adopted by translators when they encounter problems in translating gender for the directions of products’ labels from a less detailed language (English) into a higher detailed language(Arabic).The current study also strived to highlight how much the stereotype of the translator and society culture can affect the selection of a translator in choosing the grammatical gender form to detect the source language ambiguity in determining the target gender consumer. To achieve these objectives, this study depended on the descriptive analytical approach where the researchers worked on describing and analyzing the Arabic target texts (TTs) that found on some selected labels which have been gathered by the researchers. The study concluded that adding one morpheme to the target text (TT) is not just a structural change necessity but also a semantic change necessity. The study recommended that translators should be aware of linguistic, cultural and social differences between Arabic and English. Besides, they should be familiar with translating signs and images which are available on products’ labels.